6. Sensory-motor networks' topology in multiple sclerosis fatigue. Issue 4 (April 2016) - Miraglia, F.; Vecchio, F.; Porcaro, C.; Cottone, C.; Cancelli, A.; Rossini, P.M.; Tecchio, F.
Abstract : The large majority (80%) of people with multiple sclerosis (MS) complain of fatigue, which is the most disabling symptom in half of them. While the few drugs used to treat MS fatigue are limitedly useful, it was recently observed the efficacy of a personalized neuromodulation treatment, supporting the concept that interventions modifying the sensorimotor network activity balances could be suitable non-pharmacological treatments for MS fatigue. Aim of the present study is to strengthen knowledge of the brain unbalances, which proper neuromodulations should target to compensate. We collected electroencephalographic (EEG) data in 18 people with mild MS, while they were in resting state with open eyes. To ensure a wide range of fatigue, we enrolled patients to have Higher- or Lower-Fatigue based on scores of the modified Fatigue Impact Scale (mFIS). We selected the graph theory small-world index, calculated on networks of cortical nodes estimated by eLORETA, to evaluate the characteristics of left and right frontal (Motor) and parieto-occipital-temporal (Sensory) brain networks separately. Fatigue symptoms increased together with the small-world index in the Sensory network of the left dominant hemisphere. This finding hones understanding of the targets of neuromodulation interventions, indicating the sensory network of the dominant left hemisphere as a specific target.